Influence of environmental factors on the progress of root rot and web blight (Rhizoctonia solan/) of French bean - and S.K. GUPTA, SACHIN UPMANYU (Indian Phytopathology, 2005)
Root rot and web blight (Rhizoctonia solani Kuhn), an important disease of French bean, appears in the field with the onset of monsoon rains in Himachal Pradesh. A high soil moisture (80 %) and 25° C temperature were the most favourable for root rot development while web blight was best favoured at >85 percent relative humidity coupled with 25° C temperature. Continuous leaf wetness for at least 6h was essential for disease initiation, while increase in leaf wetness duration for 6-12h showed a corresponding decrease in incubation period from 36-26h, no effect on incubation period was observed with further increase in leaf wetness. Intermittent leaf wetness up to 4 cycles (12h wet! dry) resulted in high web blight severity. Simple correlation coefficient between web blight severity and mean soil moisture (r = 0.81), average relative humidity (r = 0.76) and cumulative rainfall (r = 0.73) were found to be significant and positive while partial correlation coefficients between disease severity and average relative humidity (r = 0.68) was significant and positive. Regression equation between web blight severity and environmental factors explain 86.67 percent change in the disease due to these factors. The present studies suggest that high cumulative rainfall and soil moisture, mean soil temperature ranging between 24-25° C coupled with high relative humidity (>80 %) favour the out break of web blight.